A Rare Case of Unilateral Retinitis Pigmentosa - Syntia Nusanti; Mohamad Sidik; Ari Djatikusumo; Elyas Aditya (International Journal of Retina, 2019)
Introduction: Retinitis pigmentosa (RP) is a hereditary disorder that diffusely involve photoreceptor and retinal pigment epithelial (RPE). It is characterized by progressive visual field loss and abnormal ERG. Unilateral RP is a rare condition that is usually sporadic. Clinical presentation and ancillary test results are similar to bilateral RP, with only one eye affected. In making the diagnosis of unilateral RP, clinicians must be able to rule out secondary causes, document a normal ERG in the unaffected eye, and follow-up the patient for at least 5 years to rule out bilateral but asymmetric disease. the aim of this case report is how to diagnose a rare case unilateral RP from clinical examination and ancillary tests. Methods: We report a case of a 33-year-old female with slowly progressive restriction of visual field of the left eye in the last one year before admission. Ophthalmological examination of the left eye revealed bone spicules spreading to peripheral fundus. Visual field examination revealed severely constricted visual field of the left eye. The multifocal electroretinogram (mfERG) examination showed severely depressed ERG function with reduced foveal responses. The fellow eye was within normal limit. Results: Patient was diagnosed with unilateral RP and must be followed-up for at least five years to rule out bilateral yet asymmetric disease. Making diagnosis of unilateral RP become one of the challenging case. Clinicians must be able to rule out the secondary causes that also have unilateral pigmentary retinal degeneration. Conclusion: With a good clinical examination and some simple ancillary tests, we could correctly diagnose unilateral RP. However, in this case we still need five years follow up to rule out bilateral RP yet asymmetric disease.